An integrated business process management framework for the enhancement of academic operations through digital transformation at Universities of Technology - Shange, E. M.; Nyide, C. J.; Mthalane, P. P. (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
This study investigates the impact aligning Business Process Management (BPM) practices with digital innovation can have on improving academic staff productivity and facilitating effective teaching in Universities of Technology (UoTs). The growing complexity of academic roles and the swift advancement of digital technologies have led to a reassessment of the organisation and support for academic work in higher education. Based on a wider research initiative targeting enhanced job satisfaction and productivity in academia, this paper focuses specifically on the digital processes and teaching aspects that affect academics’ performance. A quantitative approach was used in this study, driven by two main objectives: (1) to analyse existing BPM practices, and (2) to investigate the influence of digital innovation on productivity and job satisfaction among academic staff at the selected UoTs. Quantitative data were collected through an online survey involving 223 academics from two South African universities of technology and analysed using Structural Equation Modelling (SEM). The findings indicated statistically significant correlations among BPM practices, digital innovation and academic outcomes. Digital innovation significantly enhanced productivity and satisfaction, and BPM practices also had a favourable impact. The model accounted for a large portion of the variance in academic productivity and job satisfaction, demonstrating considerable predictive capability. The study proposed an integrated BPM framework designed specifically for the academic environment of UoTs. The model integrates administrative roles with educational methods and digital infrastructure, fostering effectiveness and a unified, technology-supported academic setting.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 7, Volume 9, 2025 Special Issue
Keywords: Academic staff; Business process management; Digital innovation; Productivity; Transformative learning; Education, Higher; Business -- Data processing -- Management; Workflow management systems; Universities and colleges -- South Africa